KOMITE SEKOLAH DAN MUTU PENDIDIKAN (Mewujudkan Pendidikan Berbasis Sekolah) (Jurnal Ilmu-Ilmu Sejarah, Budaya Dan Sosial ( LENTERA ), 2014)
The quality of education will not be inexhaustible into talks a lot of people, so that itbecomes synonymous with the phenomenon that is never finished, and still a matter of discussion,both by education experts, and ordinary people.One of the efforts made by the government is imposing decentralization anddemocratization of education, and better known as âeducational autonomyâ. The realization ofthe policy by the Government of the establishment of the School Committee.Basic Law as already issued Decree of the Minister of National Education No. 044 / U /2002 on April 2, 2002 on the Board of Education and the School Committee, then DirectorGeneral of Primary and Secondary Education Decree No. 559 / C / Kep / PG / 2002 onDevelopment Team Board of Education and the School Committee.Keywords: And the quality of education the school committee